Pelatihan Literasi Digital Guru SD & MI Al Hikmah untuk Menciptakan Pembelajaran Aktif - Aimah, Siti; Mulyadi, Dodi; Safuan, Safuan; Nur, Aufa Rafika; Tihurua, Nurul Inayah; Az Zahra, Ullayah Fathina; Najikha, Anggi Uswatun; Oktaviani, Irma; Nugroho, Reesky Adi; Rupiah, Sri Nikmatu; Sobirin, Sobirin; Utomo, Cicilia San San Indah Nilla; Arumsari, Maria Dewi (Jurnal Surya Masyarakat, 2023)
The impact of the Covid-19 pandemic on the education system has altered from face-to-face learning to online learning. The sudden pandemic made teachers underprepared either psychologically or pedagogically to teach online learning. Many teachers often faced psychological pressure while preparing for online teaching due to the lack of digital literacy. Teachers now have to overcome pressures for understanding digital literacy. Teachers have issues with: 1) the lack of digital literacy mastery and/or the utilization of digital learning platforms, and 2) the lack of teachers’ ability in creating meaningful learning through the use of digital technology and/or interactive multimedia. By providing the 33 teachers with support and training in digital literacy, those issues could be resolved. The assistance is focused on how to use digital learning platforms and produce android learning and interactive multimedia videos to support the learning process in the classroom. The findings showed that teachers are becoming more knowledgeable about digital literacy, particularly as it relates to the utilization of digital learning platforms and the creation of android learning videos and interactive multimedia learning videos to support the learning process in the classroom. Through the use of digital learning platforms in the classroom, teachers can provide meaningful learning experiences to students and students can actively engage in the learning process. In addition, digital literacy helps teachers increase students’ enthusiasm in the classroom, and students’ autonomous learning.